Avaliação dos parâmetros perceptivo-auditivos e acústicos da voz de teleoperadores - Amorim, Geová Oliveira de [UNIFESP] (2010)
Objective: To evaluate perceptive and acoustic parameters of telemarketing operators voice, before and after a working day. Methods: Cross-sectional study with a 55 telemarketing operators sample - 11 men and 44 women - working in receptive mode in a call center in the city of Maceió, state of Alagoas (AL). Initially a survey was applied to identify vocal complaints. It was followed by voices perceptive and acoustic evaluation procedures, such as analysis of vocal behavior during sustained emission and sequential speech. Results: The operators referred to the following vocal complaints and its related symptoms: dry throat (64%); neck and nape pain (33%); voice failure (26%); and vocal fatigue (22%). In perceptive evaluation of vocal quality the GRBASI scale was used. For other perceptive parameters of sequential speech there were no statistically significant differences. During evaluation of phonatory indwelling voice measures the maximum time of phonation kept itself reduced for both genders before and after work, with significant difference for male operators. Acoustic evaluation did not show any relevant statistical differences between parameters, considering the beginning and the end of a working day. Conclusion: Perceptive and acoustic parameters of telemarketing operators voice did not show any statistically significant difference between pre and post-working day. Although they present a large number of vocal symptoms and reduced level of maximum phonatory indwelling voice time, which reinforces the need of these professionals to be oriented about correct vocal production habits.